Cost analysis of elective percutaneous coronary intervention and its predictors in Malaysia / Lee Kun Yun - Lee, Kun Yun (2017)
With the increasing burden of metabolic syndrome, the prevalence of coronary artery disease (CAD) is rising in Malaysia. Percutaneous coronary intervention (PCI) is a common treatment modality for CAD. Cost of PCI and other cardiac procedures are escalating with the advancement in medical technology. Scarcity of local cost evidence impedes the planning for sustainable cardiology service. Cost analysis is vital for healthcare resource allocation. Limitations in the quality and availability of patient and financial data from low- and middle-income countries (LMIC) often constrain the implementation of cost analysis. This research aimed to estimate the cost of PCI in Malaysia via a modified costing method. By evaluating the cost variation between cardiac centres, we outlined the cost-saving strategies for cardiology service in Malaysia. This cost analysis was conducted from the perspective of healthcare providers at 5 cardiac centres from January to June 2014. Clinical data was extracted from a national cardiac registry. Cost data collection was conducted using mixed method of top-down and bottom-up approaches. The primary outcome of interest was the cost of PCI hospitalization. Using a clinical event pathway, cost items under each unit of analysis are identified, valuated and calculated to produce unit cost estimates. Unit costs of interest were costs of hospital general overheads, cardiac ward admission, cardiac catheterization laboratory utilization and PCI consumable; which made up total hospitalization cost. Average cost by centre were derived with top-down approach and compared between centre. Individual-level costs were generated via mixed method to enable patient-level comparison and determination of cost predictors. Analyses included descriptive statistics, logistic regression to determine the predictors of long hospitalization and linear regression to predict increased hospitalization cost. The average total hospitalization cost for an elective PCI patient ranged from RM 11,519 to RM 14,356 at the 5 centres. The dominant cost driver was PCI consumable. Day-care iv facility resulted in 80.5% cost reduction. With a sample of 2260 patients, individual patient-level mean hospitalization cost showed a wide distribution of RM 16,999 + 7,337. Regression analysis showed number of stents as a strong cost predictor. Patients with acute coronary syndrome, presence of bifurcated lesion, involvement of left main stem artery and failed revascularization during PCI were also expected to incur higher hospitalization cost. Using the findings from this study, similar cost studies can be conducted for other healthcare services. The modified costing methods will be useful for like-minded researchers in LMIC who intend to conduct health economic evaluation in the setting of limited data availability. In conclusion, the PCI cost burden on Malaysian public cardiac centres was considerably high. PCI consumable especially cardiac stents was the biggest cost contributor. Alternative consumable procurement practice such as collaborative purchasing arrangement may deliver cost reduction. Establishment of day-care facility is another viable cost-saving strategy. The study recommendations will be vital for policy makers during decision-making on resource allocation and budget planning. This will bring us one step closer towards achieving high quality, equitable and affordable cardiology service in our country.